The first impressions of small humanoid robots modulate the process of how touch affects personality what they are. (1st February 2022) - Umeda, Naoki; Ishihara, Hisashi; Ikeda, Takashi; Asada, Minoru
Abstract : It is known that the touch sensations of robots promote or deteriorate their personality impressions, and this effect has been investigated as causal relationships between several components of touch sensations and personality impressions after touching the robots. However, how the relationships are similar among different types of robots and how the first impressions modulate the relationships have not been investigated. In this study, a data set comprising response data of adult participants for the first impressions, touch sensations, and personality impressions were collected for each of six small humanoid robots with 48 adult participants. Causal relationships from each component of the touch sensations and personality impressions were first investigated via path analysis through factor analysis. Then, we analyzed which first impressions strengthen or weaken which causal relationships via moderation analysis. As a result, totally four types of statistically significant causal relationships were found in several robots. Furthermore, one of these causal relationships, which is related to the impression of likability, is strengthened when the first impression of ' an anticipation for peaceful emotional, verbal communication ' is strong. This suggests that the first impression design is as important as touch sensations when social robot designers attempt to design personality impressions. GRAPHICAL ABSTRACT: UF0001